Financing of vocational education and training in Germany - Müller, Normann [Verfasser]; Wenzelmann, Felix [Verfasser]; Jansen, Anika [Verfasser] (My University, 2017)
"German vocational education and training attracts a good deal of attention globally because it offers young people a good way of entering the employment system. However, what are the associated costs? Although precise determination of costs is difficult in methodological terms, this article attempts to address the issue." (author's abtract ; BIBB-Doku)
Finanzierung der beruflichen Ausbildung in Deutschland
Keywords: S 1.3 Berufliche Erstausbildung; S 4.1 Finanzierungsquellen; Berufsausbildung; Bildungsfinanzierung; Ausbildungskosten